Perbedaan Keikutsertaan Hypnobirthing dengan Tingkat Kecemasan Ibu Hamil dalam Menghadapi Persalinan di Kabupaten Sidoarjo - Jayanti, Adina Fitra (Jurnal Keperawatan Muhammadiyah, 2019)
Pregnancy, childbirth and having children are a woman's nature and are awaited by every woman who has a family. Increasing gestational age, pregnant women feel increasingly anxious because they are approaching labor. Fear before childbirth is the most common fear experienced by mothers during pregnancy. Pregnant women need to take time to maintain harmony of mind and body through relaxation. One relaxation technique is hypnobirthing. Hypnobirthing is very useful to reduce pain and emotional stress during childbirth, so that mothers are more calm and can overcome the anxiety experienced by pregnant women in the face of childbirth. The purpose of this study was to determine the relationship of hypnobirthing participation with the level of anxiety of pregnant women in the face of childbirth.This research is an analytic research, using a retrospective cohort research design. The research sample was 20 people, taken randomly using purposive random sampling. Data collection includes filling out the HRS-A questionnaire. Data analysis used Wilcoxon and Mann Whitney Test.The results showed that pregnant women who followed hypnobirthing and who did not follow hypnobirthing were pre-tested and post-test, there were differences in the level of anxiety between the two groups, which was indicated by a p-value of 0.005 <0.05. Furthermore, the results of the study indicate a relationship between hypnobirthing participation and a decrease in the level of anxiety of pregnant women in the face of childbirth. This is indicated by the results of p-value 0.007 <0.05.The conclusion of this study is that there is a relationship between the participation of hypnobirthing and the level of anxiety of pregnant women in the face of childbirth. Therefore, pregnant women are expected to increase awareness in finding information about methods that can help reduce anxiety levels during pregnancy to childbirth such as one of hypnobirthing.Â Keywords: Hypnobirthing participation, Anxiety Level, Pregnant Women.